2021
DOI: 10.3390/jmmp5020035
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Blanking: Influence of Clearance, Impact Energy, and Velocity on the Blanked Surface

Abstract: In contrast to other cutting processes, adiabatic blanking typically features high blanking velocities (>3 m/s), which can lead to the formation of adiabatic shear bands in the blanking surface. The produced surfaces have excellent properties, such as high hardness, low roll-over, and low roughness. However, details about the qualitative and quantitative influence of significant process parameters on the quality of the blanked surface are still lacking. In the presented study, a variable tool is used for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In addition, a blankholder of the same clearance completes the test configuration, while the half domain is studied due to its cylindrical axisymmetric geometry as shown in Figure 1 which depicts the derived FE model developed in LS-DYNA software. Finally, a constant punch velocity of 3 m/s is applied securing adiabatic blanking conditions [1,2].…”
Section: Test Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a blankholder of the same clearance completes the test configuration, while the half domain is studied due to its cylindrical axisymmetric geometry as shown in Figure 1 which depicts the derived FE model developed in LS-DYNA software. Finally, a constant punch velocity of 3 m/s is applied securing adiabatic blanking conditions [1,2].…”
Section: Test Configurationmentioning
confidence: 99%
“…Due to its strong connection to dynamic failure, the ASB mechanism has been studied regarding its influence on peak force and fracture characteristics in case of adiabatic sheet blanking process. Winter et al [1] carried out a parametric analysis of clearance, punch velocity and impact energy on ASB formation in blanking of 22MnB5 hardened steel sheet, revealing an S-shaped shear band formulation, while also higher velocity and lower clearance increased material sensitivity against ASB occurance. Further, Schmitz et al [2] revealed that shear bands expand along S-shaped traces in case of adiabatic blanking of high-strength steels, also obtaining that material strain rate hardening behavior strongly affects the width and hardness of ASB.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Winter et al [6] investigated ASB evolution in adiabatic blanking of 22MnB5 steel by conducting parametric analyses regarding clearance, blanking velocity, and impact energy. Both experiments and finite element (FE) simulations in LS-DYNA were carried out, revealing S-shaped ASB for clearance below 6.67% of sheet thickness and velocity greater than 7 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially relevant when it comes to localization and a correspondingly strong increase in the local strain, strain rate, and temperature. An exemplary application where this effect becomes relevant is the formation of adiabatic shear bands in high-speed impact cutting [14]. The two effects of strain hardening and thermal softening superpose each other so that accurate and thermo-mechanically consistent material modeling is complicated significantly.…”
Section: Introductionmentioning
confidence: 99%